Desentralisasi Dalam Meningkatkan Efisiensi Pelayanan Publik: Studi Literatur Terhadap Program Teras Madukara di Kabupaten Purwakarta - Rahmatan, Didan Fauzan; Sri Kartini, Dede (Universitas Serang Raya, 2025)
This study aims to analyze how decentralization policies can enhance the efficiency of public service delivery through a case study of the Teras Madukara program in Purwakarta Regency. The main focus of this study is to evaluate the extent to which the program realizes the principles of responsive, equitable, and satisfactory public services, based on the public choice theory framework proposed by Dennis A. Rondinelli. Three key indicators are used in the analysis: (1) responsiveness of public institutions; (2) the ability to meet public commodity demands; and (3) the provision of satisfactory public services. This research employs a descriptive qualitative approach through a literature study method, drawing on secondary data from scientific journals, books, policy documents, and official government reports. The findings indicate that the Teras Madukara program effectively addresses the geographical challenges of Purwakarta Regency by delivering 407 types of public services to five sub-districts, including remote areas with limited access. The program has been shown to improve service efficiency and received positive responses from the public, as reflected in a satisfaction index of 87.69% and the recognition of the Bale Madukara Public Service Mall with the Prima predicate by the Ministry of Administrative and Bureaucratic Reform (KemenPAN-RB). Compared to similar programs such as Dokkar Salman in Wonosobo Regency and Cedak Mas in Tuban Regency, Teras Madukara demonstrates advantages in terms of service integration and its mini public service mall (MPP) model at the sub-district level. These findings affirm that decentralization, when implemented adaptively and based on local needs, can strengthen democratic, efficient, and inclusive public service governance. Keywords: Decentralization, Public Service, Efficiency, Teras Madukara, Public Choice